2013
DOI: 10.1007/s00497-013-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic separation of autonomous endosperm formation (AutE) from the two other components of apomixis in Hieracium

Abstract: In apomictic Hieracium subgenus Pilosella species, embryo sacs develop in ovules without meiosis. Embryo and endosperm formation then occur without fertilization, producing seeds with a maternal genotype encased in a fruit (achene). Genetic analyses in H. praealtum indicate a dominant locus (LOA) controls meiotic avoidance, and another dominant locus (LOP) controls both fertilization-independent embryogenesis and endosperm formation. While cytologically examining developmental events in ovules of progeny from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…Similarly, apospory and parthenogenesis are controlled by two independent loci in Hypericum, Poa, Hieracium, and Cenchrus species (Albertini et al 2001;Catanach et al 2006;Schallau et al 2010;Conner et al 2013). Genetic studies in Hieracium, which is also capable of fertilization-independent endosperm formation, have revealed that this trait can also segregate independently of the other two apomictic components (Ogawa et al 2013). Interestingly, characterized gamma deletion mutants have revealed that sexual reproduction is the default pathway in apomictic Hieracium praealtum.…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…Similarly, apospory and parthenogenesis are controlled by two independent loci in Hypericum, Poa, Hieracium, and Cenchrus species (Albertini et al 2001;Catanach et al 2006;Schallau et al 2010;Conner et al 2013). Genetic studies in Hieracium, which is also capable of fertilization-independent endosperm formation, have revealed that this trait can also segregate independently of the other two apomictic components (Ogawa et al 2013). Interestingly, characterized gamma deletion mutants have revealed that sexual reproduction is the default pathway in apomictic Hieracium praealtum.…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…Moreover, Arabidopsis and rice artificial plants producing male and female clonal diploid gametes have already been obtained [21, 22]. On the other hand, several research groups have been focused on the dissection of the genomic region controlling the trait in natural apomictic species [23–38]. In the grasses, the genomic region controlling aposporous apomixis was characterized as a single locus (apomixis controlling locus or ACL) which is often large, complex and recalcitrant to recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous endosperm formation is controlled by the independent locus AutE in P. piloselloides isolate D36 (formerly H. piloselloides) and is genetically separable from LOA and fertilizationindependent embryogenesis. Markers linked to AutE and its chromosomal location remain to be identified (Ogawa et al, 2013). The genes responsible for apomixis function at all three loci are unknown.…”
Section: Introductionmentioning
confidence: 99%